Giáo trình thành ngữ, tục ngữ 汉语口语习惯用语教程 - Thẩm, Kiến Hoa (Đại học ngôn ngữ Bắc Kinh, 2020)
Useful intermediate-level text, this book teaches about 500 common idioms over 20 lessons, with pinyin, English definitions of the terms but with examples in Chinese.